Reorientasi Dikotomis Ilmu Agama dan Umum Melalui Pendekatan Analisis Bibliometrik - Huda, Ali Anhar Syi'bul; Hamdi, Hamdi; Ridani, Muhammad Noor; Nurhuda, Abid (Kamaya: Jurnal Ilmu Agama, 2024)
In a world where technology is rapidly advancing, religion is often overshadowed by the growing emphasis on general science. This has led to a widening gap between religious studies and general science. This research aims to bridge this gap and challenge the dichotomy between religious and general sciences through a bibliometric analysis. Using a bibliometric approach, the study explores existing literature to identify gaps in research. Data was gathered from 500 articles sourced from Google Scholar through the Publish or Perish (PoP) tool, focusing on publications from 2014 to 2024. The analysis utilized VOSViewer for mapping and Microsoft Word for basic analysis. The findings reveal a significant increase in studies addressing the dichotomy between religious and general sciences over the last decade. The majority of publications are from e-journals, with 359 articles, while e-books accounted for 100 publications. The research also identifies seven key researchers in this field, including Hasan Baharun, Bashori, Afiful Ikhwan, Istikomah, Mujibor Rohman & Miftahur Rohman, Tabrani ZA, and Muhamad Khoirul Umam, with each contributing at least three publications, except Mujibor Rohman, who has one. The VOSViewer analysis identified three clusters within the research development: Cluster 1 with eight items, Cluster 2 with six items, and Cluster 3 with five items. The most common keywords found were "general science," "pesantren," and "Islamic religious education." This study highlights the growing interest in bridging religious and general sciences and suggests a need to reorient perspectives to address the imbalance.